Exploring the induction of preproinsulin-specific Foxp3+ CD4+ Treg cells that inhibit CD8+ T cell-mediated autoimmune diabetes by DNA vaccination - Stifter, Katja (2016)
DNA vaccination is a promising strategy to induce effector T cells but also regulatory Foxp3(+) CD25(+) CD4(+) Treg cells and inhibit autoimmune disorders such as type 1 diabetes. Little is known about the antigen requirements that facilitate priming of Treg cells but not autoreactive effector CD8(+) T cells. We have shown that the injection of preproinsulin (ppins)-expressing pCI/ppins vector into PD-1- or PD-L1-deficient mice induced K(b)/A12-21-monospecific CD8(+) T cells and autoimmune diabetes. A pCI/ppinsΔA12-21 vector (lacking the critical K(b)/A12-21 epitope) did not induce autoimmune diabetes but elicited a systemic Foxp3(+) CD25(+) Treg cell immunity that suppressed diabetes induction by a subsequent injection of the diabetogenic pCI/ppins. TGF-β expression was significantly enhanced in the Foxp3(+) CD25(+) Treg cell population of vaccinated/ppins-primed mice. Ablation of Treg cells in vaccinated/ppins-primed mice by anti-CD25 antibody treatment abolished the protective effect of the vaccine and enabled diabetes induction by pCI/ppins. Adoptive transfer of Treg cells from vaccinated/ppins-primed mice into PD-L1(-/-) hosts efficiently suppressed diabetes induction by pCI/ppins. We narrowed down the Treg-stimulating domain to a 15-residue ppins76-90 peptide. Vaccine-induced Treg cells thus play a crucial role in the control of de novo primed autoreactive effector CD8(+) T cells in this diabetes model.